Photography : the key concepts - Bate, David (Oxford ; New York : Berg, 2009)
History -- Photography theory -- Documentary and story-telling -- Looking at portraits -- In the landscape -- The rhetoric of still life -- Art photography -- Global photography.
Includes bibliographical references and index.
boek